2024
DOI: 10.1111/brv.13050
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of Greater Antillean freshwater fishes, with a review of competing hypotheses

Yibril Massip‐Veloso,
Christopher W. Hoagstrom,
Caleb D. McMahan
et al.

Abstract: In biogeography, vicariance and long‐distance dispersal are often characterised as competing scenarios. However, they are related concepts, both relying on collective geological, ecological, and phylogenetic evidence. This is illustrated by freshwater fishes, which may immigrate to islands either when freshwater connections are temporarily present and later severed (vicariance), or by unusual means when ocean gaps are crossed (long‐distance dispersal). Marine barriers have a strong filtering effect on freshwat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 226 publications
0
1
0
Order By: Relevance
“…Matschiner et al (2017) suggested two early cases of transoceanic dispersal of cichlids from Madagascar to continental Africa and from there to South America before their radiations in those continents. Similarly, a recent study suggests about 16-17 historical events of oceanic dispersal (mostly of cypronodontiforms) to the Greater Antilles over the last 51 million years (Massip-Veloso et al, 2024).…”
Section: Discussionmentioning
confidence: 87%
“…Matschiner et al (2017) suggested two early cases of transoceanic dispersal of cichlids from Madagascar to continental Africa and from there to South America before their radiations in those continents. Similarly, a recent study suggests about 16-17 historical events of oceanic dispersal (mostly of cypronodontiforms) to the Greater Antilles over the last 51 million years (Massip-Veloso et al, 2024).…”
Section: Discussionmentioning
confidence: 87%